Cielesność w Chmurdalii Joanny Bator (Heteroglossia – studia kulturoznawczo-filologiczne, 2022)
This article aims to problematize the issue of corporeality in Joanna Bator’s novel Chmurdalia, whitch was written in 2010. The aim of the sketch is to discuss and conceptualize the approaches to corporeality presented in the novel and to take into account such an approach to the human body that would take into account its specific subjective character. It is also advisable to verify the theses about the fundamental role of corporeality in Bator’s novel and about the subjectivity of the body. The last point is directly related to the – extremely important for my deliberations – elements of Maurice Merleau-Ponty’s concept. His theory seems to be especially valuable in the face of the phenomenon of “looking at the body”” that is taking place today. According to the philosopher, the uniqueness of corporeality manifests itself in the fact that the body is not limited only to what is seen, but is also what it watches. The text includes a reflection on the present Chmurdalia shots of corporeality related to the corporeality of the main character, Dominika Chmura, as well as the body of Dominika’s friend, Sara Jackson, and the hairdresser Tadeusz Kruk’s theme.